Peningkatan Kemampuan Orientasi Dan Mobilitas Melalui Penerapan Teknik Pendamping Awas Pada Siswa Low Vision Kelas X SLB - Syamsuddin Syamsuddin; Faisal Faisal; Purwakahadi Purwakahadi; Thyna Suhartini (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study examines the low ability of orientation and mobility of low vision students in Polewali State Special School. The data collection technique used is an action test. The subjects in this study were 1 low vision student in class X at Polewali State SLB. This study uses an experimental method using Single Subject Research (SSR) with an A-B-A design. With the application of the watchful companion technique, it can improve the orientation and mobility skills of low vision students. The data obtained were analyzed through descriptive statistics and displayed graphs. The results of this study concluded that through the application of a watchful companion technique, the ability of orientation and mobility of low vision students of class X at SLB Negeri Polewali could be improved.